Ginkgo Biloba Leaf Extract Attenuates Atherosclerosis in Streptozotocin-Induced Diabetic ApoE-/- Mice by Inhibiting Endoplasmic Reticulum Stress via Restoration of Autophagy through the mTOR Signaling Pathway. (18th March 2019) - Tian, Jinfan; Popal, Mohammad Sharif; Liu, Yanfei; Gao, Rui; Lyu, Shuzheng; Chen, Keji; Liu, Yue
Abstract : Background . There is a crosstalk between endoplasmic reticulum stress (ERS) and autophagy, and autophagy could attenuate endoplasmic reticulum stress-mediated apoptosis. Ginkgo biloba leaf extract (GBE) exerts vascular protection functions. The purpose of the present study is to investigate the role of autophagy in diabetic atherosclerosis (AS) and the effect of GBE on autophagy and ERS. Methods . Network pharmacology was utilized to predict the targets and pathways of the active chemical compounds of Gingko biloba leaf to attenuate AS. ApoE -/- mice were rendered diabetic by intraperitoneal ingestion with streptozotocin combined with a high-fat diet. The diabetic mice were divided into five groups: model group, atorvastatin group, rapamycin group, and low- and high-dose GBE groups. Serum and tissue markers of autophagy or ERS markers, including the protein expression, were examined. Results . The mammalian target of rapamycin (mTOR) and NF- κ B signaling pathways were targeted by the active chemical compounds of GBE to attenuate AS predicted by network pharmacology. GBE reduced the plaque area/lumen area and the plaque lipid deposition area/intimal area and inhibited the expressions of CD68, MMP2, and MMP9. Rapamycin and GBE inhibited the expression of mTOR and SQSTM1/p62 which increased in the aorta of diabetic mice. In addition, GBE reduced the expression of ERS markers in diabetic mice. GBE reduced the serum lipid metabolism levels, blood glucose, and inflammatory cytokines. Conclusion . Impaired autophagy and overactive endoplasmic reticulum stress contributed to diabetic atherosclerosis. mTOR inhibitor rapamycin and GBE attenuated diabetic atherosclerosis by inhibiting ERS via restoration of autophagy through inhibition of mTOR.